(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2025)
This article develops the initial process of immersion and connection- building between the authors, a teacher and student from the Faculty of Human Sciences, of the Universidad Nacional de La Pampa, and the murga group “Bien de Barrio”. The experience articulated organized programmatic community practices, in this case, from the outreach project “Memorias Maricas Pampeanas” in 2024. The text explores different moments of the experience, considering the theoretical foundations of both critical outreach and our own transfeminist political praxis. As a whole, we understand that it highlights the distinct value of experiencing, teaching and learning from/with love.